34 WITNESSING INTIMATE PARTNER VIOLENCE (IPV) AS A CHILD DOES NOT INCREASE THE LIKELIHOOD OF BECOMING AN ADULT AN ADULT VICTIM OF INTIMATE PARTNER VIOLENCE. Issue 1 (1st January 2007) - Ernst, A.; del Castillo, C.; Weiss, S.; Combs, S. M.; D'Angelo, J. A.; Feuchter, A. C.; Hegyi, M. A.; Marvez-Valls, E.; Clark, R.; Coffman, B.
Abstract : Objective: Intimate partner violence (IPV) perpetration has been associated with alcohol, drug use, and witnessing IPV as a child. Associations between being a child witness and being an IPV victim are not well established. The hypothesis of the present study was that child witnesses were different from non-child witnesses in race, education, gender, insurance, children in the home, marital status, income, age, and IPV positivity. Methods: A confidential touch screen data entry program was used to collect demographic data. The Ongoing Violence Assessment Tool (OVAT), a validated screen of ongoing IPV, was used during a prospective study that used randomized 4-hour shifts in an academic ED. Randomized 4-hour shifts were determined via a random numbers table. Subjects were given an informational consent form before participation, following IRB procedure. Trained research associates approached potential subjects during shifts to enter the study. The power of the study was 80% to show a difference of 20% between groups, with a total of 260 patients entered and 20% positive for IPV. Results: 280 subjects were entered in the study. Subjects were 50% male; 46% were Hispanic and 36% were Caucasian. Seventy-two (26%) subjects were child witnesses and 208 (74%) were non-child witnesses. Overall, 63 (23.5%) were positive for ongoing IPV. By univariate analysis there was no significant correlation of child witnessing of IPV with race, education, gender, insurance, children in the home, or marital status. Child witnesses were also not more likely to drink, use drugs, or have spouses who drink or use drugs. Correlation of child witnessing with IPV positivity ( p = .07) was borderline in that 23 of 74 (32%) of the child witnesses and 39 of 184 (21%) of the non-child witnesses were positive for IPV. Significant correlations with child witnessing included age less than 40 (OR 3.9; 95% CI 1.7-8.9), income less than 20, 000/year (OR 5.2; 95% CI 1.8-14.7), and abuse as a child (OR 9.8; 95% CI 4.6-20.7). Conclusions: Child witnesses were more likely to have lower income, be younger, and have been abused as a child. They were not more likely to be positive for ongoing IPV, although there was a trend in that direction.